Explorations in the Dialect of Australian Aboriginal Preschool Children - Webb, Gwendalyn (Curtin University, 2017)
This longitudinal research explored the use of Aboriginal English (AE) dialect by Australian Aboriginal preschool children. Data from educator-child interactions was analysed for features of AE and change in dialect density across contexts. Interview data gathered from educators and carers about the children’s communicative competency was analysed qualitatively. Results confirmed Aboriginal children’s use of AE dialect and highlighted factors perceived by participants to affect their language and literacy development. Directions for future research are indicated.